Indicators and protocol to identify sustainable post harvest management practices in rice production in Vietnam and Myanmar - CGIAR Research Program on Rice (2021)
The indicators and standards for sustainable post harvest management practices were incorporated in the Sustainable Rice Standards. They were applied to for different postharvest management practices in Myanmar, and uptaken and adapted to develop the method for postharvest loss indicators under the LACP project in LAO-republic.